Health Governance and Covid19 Pandemic in South Asia: An Afghanistan Perspective - Masomy, Masom Jan; Humayun, Sheikh I. (South Asian Journal of Social Sciences and Humanities, 2021)
For more than a year, countries and the international community are involved in the fight against the Covid19 pandemic. Different countries have also been making tireless attempts to produce a vaccine to contain the virus. The United States and England have started to offer vaccination doses to their citizens in action recently. Efforts by India, China, and other countries have begun to provide Covid19 vaccines to the people and the world. With the spreading of covid19 from China to the world beyond, countries were put on a difficult path that affected their national economies, particularly developing countries. In this regard, South Asia faced difficulties while the Covid19 spread into the region. In this paper, the gaps and drawbacks of the South Asia health system have been explored and pointed out its challenges and deficiencies amid the Covid19 pandemic in general. Besides, the paper has also examined the case study of Afghanistan regarding the fight against Covid19. Common challenges have been highlighted that affected the combat against Coronavirus in Afghanistan. The flawed health system, mismanagement, and misappropriation of the Covid19 budget allocated and donated by the government, international community, and donor countries have also been explored and analyzed, making the paper’s core issue.